Value Co-creation Through Digitalisation: From a Micro-level to a Meso-level Approach - Chen Zhou, Yiran; Tsvetkova, Anastasia (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This study identifies micro-to-meso level hindrances for value co-creation through digitalisation at port operations. Digitalisation in ports faces significant challenges due to complex, interdependent actor relationships. This study explores how micro-level hindrances affect meso-level value co-creation in a port digitalisation context. Based on an explorative case study of a RoPax port digitalisation project, we identified hindrances across levels could constrain and interdepend on each other. Micro-level hindrances within an organisation, such as — lack of digitalisation leads, limited operational data, outdated digital infrastructure and security concerns — could reinforce six hindrances on meso-level: 1) unaware co-creators, 2) lack of collective leadership for digitalisation, 3) limited data accessibility, 4) low inter-organisational resource compatibility, 5) misaligned or misunderstood value co-creation targets, 6) resistant to change.